2013
DOI: 10.4103/2278-960x.112576
|View full text |Cite
|
Sign up to set email alerts
|

Screening for cervical cancer: Experience from a university hospital in north western Nigeria (2007-2009)

Abstract: Background: Cervical cancer is the most common gynecological cancer among women in Nigeria. The incidence is on the increase and poses a public health problem. The etiological agent is the human papilloma virus that is sexual transmitted. The cervical cancer incidence is related to lifestyle, poverty and sexual practices. Fortunately, it is a preventable disease as it is preceded by a pre-invasive phase that can be detected and treated. There is paucity of report in literature on cervical cancer screening in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 11 publications
1
16
1
Order By: Relevance
“…The Pattern of presentation was disturbing, as most of the patients presented in the late stages of the cancer. Several previous studies have reported late stage presentations [19][20][21][22][23]. Majority of cancer cases were diagnosed at advanced stages probably due to lack of effective screening and early detection services, in addition to the …”
Section: Resultsmentioning
confidence: 99%
“…The Pattern of presentation was disturbing, as most of the patients presented in the late stages of the cancer. Several previous studies have reported late stage presentations [19][20][21][22][23]. Majority of cancer cases were diagnosed at advanced stages probably due to lack of effective screening and early detection services, in addition to the …”
Section: Resultsmentioning
confidence: 99%
“…It causes death of women and weakens the family/community fabric [18]. In Nigeria, cervical-cancer results in about $3.3 million/ Disability Adjusted Life years (DALYS) lost annually in terms of man-hour loss and medical costs [4][5][6][7].…”
Section: Burden Of Cervical-cancermentioning
confidence: 99%
“…Though a single visit cervicalcancer screening could save more than 6,000 Nigerian women annually, uptake is low [8]. Out of thirteen different studies on cervical-cancer screening uptake in Nigeria reviewed, nine (69.2%) showed cervical-cancer screening uptake < 5.3%, while four (30.8%) recorded uptake > 5.3% [4][5][6]8,9,[19][20][21][22][23][24][25][26] against 75% with screening rate > 5.0% in developed countries [18].…”
Section: Cervical-cancer Screening Uptake In Nigeriamentioning
confidence: 99%
See 2 more Smart Citations